Inventarisasi anggrek di kawasan hutan Desa Tanjung Sakti Kecamatan Tanjung Sakti Pumi Kabupaten Lahat sebagai data dasar dalam upaya introduksi anggrek di Semambu Edu-Land Desa Pulau Semambu Kabupaten Ogan Ilir - Doni Setiawan; Ina Aprilia; Guntur Pragustiandi; Winda Indrianti; Rio Firman Saputra (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
This study aims to inventory of the types on orchids found in the forest area of Tanjung Sakti Village, Tanjung Sakti Pumi District, Lahat Regency. This research was motivated by the first plan of conservation efforts by introducing several types of orchids found to the Semambu Edu-land area for conservation. This study used an exploratory method, while data collection was carried out by method of explore as far as 3 km following the path of forest areas and river flow. The results of this study found that 26 species of orchids are included in 21 genera consisting of orchids based on their habitus of 14 epiphytic orchids and 5 terrestrial orchids, and 2 orchids were found in both. Based on the IUCN Redlist category, it was found that one species of orchid whose conservation status was Endangered, namely Papiophedillum superbiens, and of the 26 species found from the initial research, 11 species of orchids were introduced in Semambu Edu-land, Pulau Semambu Village.